Mental self-regulation and implementation of preparedness in competitions among athletes with different levels of hardiness - Lovyagina, A. E.; Ilyina, N. L.; Lukina, S. M.; Shindrikova, E. V. (Theory and Practice of Physical Culture, 2023)
Objective of the study was a comparative analysis of the indicators of mental self-regulation and physical fitness performance at the competitions among athletes with different hardinesslevel.